The Femal Narrative in Anisa Abboud’s "Bab Al-Hayra" - القصيري, نضال (Latakia University Journal - Arts and Humanities Sciences Series, 2023)
This research revolves on approaching female narrative in Anisa Abboud’s "Bab Al-Hayra". The paper attempts to uncover the narrative techniques employed by the novelist in this novel and focus on the political, social and moral issues articulated in the novel. Abboud’s narration trespasses the femal self to announce its presence through dealing with realistic problems that unit with this self that is capable of addressing these issues daringly, efficiently and effectively, the thing that resulted in a cognitively-saturated narrative discourse. The paper concludes that the novelist celebrates a conglomeration of narrative techniques (Monologue, Remember, Free Association) that reveal her fondness of modernizing her narrative techniques and being influenced by modern technologies, which were beneficial for cenimatology through the use of witness narrator technique. It also illuminates the novelist’s attempts to address problematic issues from a feminist perspective, in an attempt to reconstruct the social, political and moral reality.